The Effect of Teamwork on the Internal Communication Performance of Employees at the Liukang Kalma Office - Sriwahyudi, Nurul; Tawe, Amiruddin; Natsir, Uhud Darmawan (Jurnal Riset Bisnis, Manajemen, dan Ilmu Ekonomi, 2025)
This study aims to explore the effect of teamwork on the internal communication performance of employees in Liukang Kalma Subdistrict, Pangkep Regency. In the context of public organisations, internal communication is a crucial aspect that affects operational effectiveness and collaboration within teams. This research was conducted through a literature review approach by collecting and analysing various literature related to teamwork, communication, and employee performance. The results show that effective teamwork contributes significantly to improving internal communication performance. This improvement is demonstrated through a more harmonious working atmosphere, increased information sharing, and reduced conflict among team members. This study also identified supporting factors such as trust, motivation, and commitment of team members that play an important role in achieving better communication performance. With a deeper understanding of the influence of teamwork, it is hoped that employees can optimise internal communication performance to achieve organisational goals effectively. These findings are expected to serve as a reference for decision makers in improving teamwork strategies in the government environment. Penelitian ini bertujuan untuk mengkaji pengaruh kerja sama tim terhadap kinerja komunikasi internal karyawan di Kecamatan Liukang Kalma, Kabupaten Pangkep. Dalam konteks organisasi publik, komunikasi internal merupakan aspek krusial yang memengaruhi efektivitas operasional dan kolaborasi di dalam tim. Penelitian ini dilakukan melalui pendekatan tinjauan literatur dengan mengumpulkan dan menganalisis berbagai literatur terkait kerja sama tim, komunikasi, dan kinerja karyawan. Hasil penelitian menunjukkan bahwa kerja sama tim yang efektif berkontribusi secara signifikan dalam meningkatkan kinerja komunikasi internal. Peningkatan ini ditunjukkan melalui suasana kerja yang lebih harmonis, peningkatan berbagi informasi, dan penurunan konflik di antara anggota tim. Penelitian ini juga mengidentifikasi faktor pendukung seperti kepercayaan, motivasi, dan komitmen anggota tim yang berperan penting dalam mencapai kinerja komunikasi yang lebih baik. Dengan pemahaman yang lebih mendalam tentang pengaruh kerja sama tim, diharapkan karyawan dapat mengoptimalkan kinerja komunikasi internal untuk mencapai tujuan organisasi secara efektif. Temuan ini diharapkan dapat menjadi acuan bagi pemangku kepentingan dalam meningkatkan strategi kerja sama tim di lingkungan pemerintahan.